Integrating Traditional Islamic Pedagogy and Communicative Language Teaching: The Use of the Muhādatsah Method in Arabic Speaking Instruction - Arif, Widodo; Nisa, Khoirun; Sa’adah, Alfina Nuris; Safitri, Eli (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
Arabic language competence is essential in pesantren education for understanding classical texts, engaging in religious discourse, and academic communication. Despite emphasis on grammar and translation, many students lack active speaking skills (mahārah al-kalām). This study examines the implementation of the muhādatsah method at Sunan Drajat Islamic Boarding School, Lamongan, analyzing student responses and its impact on speaking skills. Using a qualitative classroom action research design over two cycles with third-semester students, speaking performance was assessed via a rubric covering fluency, pronunciation, vocabulary, grammar, and communicative confidence. Data were collected through observations, interviews, field notes, and pre- and post-assessments, analyzed descriptively with simple score comparisons. Findings indicate that systematic muhādatsah practice improved fluency, pronunciation, vocabulary, and confidence, fostering engagement. Despite small sample size and context-specific limitations, muhādatsah is effective for enhancing Arabic speaking skills in pesantren contexts.